PROBLEM SOLVING ANALYSIS OF DISTANCE PRACTICUM IN PHYSICS SUBJECTS AT MTS DDI SEPPANGE - Napsa, Napsawati; Kadir, Fitriani (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to analyze the extent to which problem solving applied at MTs DDI Seppange can overcome the difficulties faced by students in the implementation of distance practicum. To achieve this goal, this research was carried out at the MTs DDI Seppange school, Bone, South Sulawesi with the research sample being class IX students at MTs DDI Seppange in the 2019/2020 school year totaling 24 people and science subject teachers at MTS DDI Seppange. The research steps include: practicum planning, practicum implementation, and practicum result evaluation. While the method of data collection is done by observation, interviews and questionnaires. Furthermore, the data obtained were analyzed descriptively qualitatively. The results obtained indicate that the solution applied in this study is a distance practicum guide by utilizing easily available tools and materials and the hands-on method is feasible to apply.